The Fight: Symbolic Expression and Validation of Masculinity in Working Class Tavern Culture - Hochstetler, Andy (American journal of criminal justice, 2014)
This study examines the role that masculinity plays in men’s decisions to participate in bar fights. The data were obtained via semi-structured interviews with adult, White males in Louisiana who had a history of fighting. We argue that specific elements of fighting events represent symbolic attempts at attaining and maintaining honor and status, which many men in working class culture equate with masculine identity. While winning fights was seen as important, participants suggest that willingness to fight in the right circumstances builds character, develops an honorable reputation, and prevents negative labels. We further argue that pursuit of symbolic masculinity is important to working class men, who possess fewer alternative avenues for achieving status than do those from higher social ranks.